Comprehensive comparison of industrial cannabinoid extraction techniques: Evaluation of the most relevant patents and studies at pilot scale - López-Olmos, Cristina; García-Valverde, María Teresa; Hidalgo, Jesús; Ferrerio-Vera, Carlos; Sánchez de Medina, Verónica (Frontiers in Natural Products, 2022)
Cannabinoids are gaining attention in many sectors, such as the pharmaceutical or the medical sector. To date, several techniques have been applied for cannabis extraction at industrial scale, from conventional to alternative techniques. The conventional methods are liquid solvent extraction, including polar and non-polar solvents, such as ethanol, hexane, petroleum ether and other solvent extraction. Pressurized gas extraction is another conventional method and comprises gaseous hydrocarbon extraction such as n-butane and n-propane, supercritical or subcritical carbon dioxide extraction, and extraction using a refrigerant gas such as 1,1,1,2-tetrafluoroethane (HFC 134a). Alternative extraction methods include microwave assisted extraction (MAE), ultrasound assisted extraction (UAE), hydrodynamic cavitation and pulsed electric fields (PEF). This review thoroughly analyses and compares the main extraction techniques as well as extraction technologies found in the patent literature at industrial scale. In addition, several aspects of the pretreatment of the cannabis plant material and its influence on extraction are also discussed.